CONSUMER PROTECTION IN THE PROVISION OF HEALTH SERVICES - Jaloliddin Askarov (Scholar Express Journals, 2024)
The article provides a comprehensive overview of consumer rights within the healthcare sector, emphasizing the importance of legal and ethical frameworks in safeguarding patient interests. It highlights the legislative efforts in Uzbekistan, alongside international perspectives, to ensure that healthcare delivery aligns with established standards and respects patient autonomy. The discussion acknowledges the challenges inherent in the healthcare service market, including the variability in medical service quality and the complexities introduced by telemedicine. The article advocates for enhanced medical and legal literacy among consumers to empower them in exercising their rights effectively. It also underscores the necessity for healthcare providers and insurance companies to uphold high standards of care, guided by ethical practices and regulatory compliance, to foster a healthcare environment that prioritizes patient well-being and transparent communication.
Keywords: Law; medical service; consumer protection; rights and responsibilities